2013
DOI: 10.4304/tpls.3.7.1250-1257
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Written Corrective Feedback Techniques on EFL Students’ Control over Grammatical Construction of Their Written English

Abstract: There has been a controversy over the usefulness of the written corrective feedback (WCF) on the accuracy of ESL/EFL learners' writingespecially after Truscott's assertion that grammar correction is pointless and harmful (1996). This study presents the findings of an investigation of the impact of WCF on 90 intermediate Iranian EFL students. The participants were separated into three groups; then they randomly received direct, indirect or no correction feedback. They created three pieces of writing, pre-test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
(32 reference statements)
2
17
0
1
Order By: Relevance
“…Another example is a study conducted by Ahmadi-Azadi (2014) who found that indirect CF had a positive influence on learners' accurate use of all selected grammatical structures. In another study, indirect CF group outperformed direct CF group in delayed posttest (Maleki & Eslami, 2013). Storch and Wigglesworth (2010) also assert that indirect corrective feedback facilitates the uptake and retention of writing accuracy compared to direct corrective feedback.…”
Section: Indirect Corrective Feedbackmentioning
confidence: 95%
“…Another example is a study conducted by Ahmadi-Azadi (2014) who found that indirect CF had a positive influence on learners' accurate use of all selected grammatical structures. In another study, indirect CF group outperformed direct CF group in delayed posttest (Maleki & Eslami, 2013). Storch and Wigglesworth (2010) also assert that indirect corrective feedback facilitates the uptake and retention of writing accuracy compared to direct corrective feedback.…”
Section: Indirect Corrective Feedbackmentioning
confidence: 95%
“…Indirect feedback occurs when the students are informed in some way that an error exists but are not provided with the correct form, thus placing the burden of spotting the erroneous forms on students. The experts in the field argue that indirect feedback is superior for most students, because it involves them in guided learning and problem solving (Maleki & Eslami, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that indirect WCF is more effective for long term improvement than direct WCF (Ferris & Helt, 2000;Ji, 2015;Lu, 2010;Maleki & Eslami, 2013;Moser, 2010). Students need to process the codes, understand their errors and find the solutions themselves (Ferris, 1995;Lalande, 1982).…”
Section: Main Effect Of Wcf Typementioning
confidence: 99%